Jesuits in Africa A Historical Narrative from Ignatius of Loyola to Pedro Arrupe - Festo Mkenda, SJ (Brill, 2022)
Jesuits have been in Africa since the founding of their order, yet their history there remains poorly researched. Although scholars have begun to focus on specific regions such as Congo, Ethiopia, and Zimbabwe, a comprehensive picture of the entire Jesuit experience on the continent has hitherto been lacking. In a condensed yet accessible way, Jesuits in Africa fills that lacuna. Narrating the story century by century from the time of St. Ignatius of Loyola (c.1491-1556), founder of the Jesuits, to that of Pedro Arrupe (1907-91, in office 1965-83), twenty-eighth superior general of the Society, this book makes Jesuit history in Africa available to a general readership while offering scholars a broad view in which specialized topics can be conceived and deepened.